2018
DOI: 10.1007/s00401-018-1817-z
|View full text |Cite
|
Sign up to set email alerts
|

NHLRC2 variants identified in patients with fibrosis, neurodegeneration, and cerebral angiomatosis (FINCA): characterisation of a novel cerebropulmonary disease

Abstract: A novel multi-organ disease that is fatal in early childhood was identified in three patients from two non-consanguineous families. These children were born asymptomatic but at the age of 2 months they manifested progressive multi-organ symptoms resembling no previously known disease. The main clinical features included progressive cerebropulmonary symptoms, malabsorption, progressive growth failure, recurrent infections, chronic haemolytic anaemia and transient liver dysfunction. In the affected children, neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(74 citation statements)
references
References 27 publications
4
70
0
Order By: Relevance
“…While NHLRC2 has a CCINC motif, structural homologues have SCINC (DipZ), WCPTC (DsbF), WCPSC (DsbE) and WCVPC (TlpA). Consistent with this difference, we have previously shown that the Trx-like domain of NHLRC2 does not contain oxidoreductase activity in a classical insulin reduction assay using either the full-length protein or the isolated Trx-like domain [ 2 ] suggesting that it is not involved in thiol-disulfide exchange.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…While NHLRC2 has a CCINC motif, structural homologues have SCINC (DipZ), WCPTC (DsbF), WCPSC (DsbE) and WCVPC (TlpA). Consistent with this difference, we have previously shown that the Trx-like domain of NHLRC2 does not contain oxidoreductase activity in a classical insulin reduction assay using either the full-length protein or the isolated Trx-like domain [ 2 ] suggesting that it is not involved in thiol-disulfide exchange.…”
Section: Resultssupporting
confidence: 65%
“…Previously, NHLRC2 homologs were thought to be limited to animalia [ 1 , 2 ]. However, homologs can be found across different kingdoms of life, including in prokaryotes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations